Electrospun Fiber Alignment Guides Osteogenesis and Matrix Organization Differentially in Two Different Osteogenic Cell Types - Delaine-Smith, Robin M.; Hann, Alice Jane; Green, Nicola H.; Reilly, Gwendolen Clair (Frontiers in Bioengineering and Biotechnology, 2021)
Biomimetic replication of the structural anisotropy of musculoskeletal tissues is important to restore proper tissue mechanics and function. Physical cues from the local micro-environment, such as matrix fibre orientation, may influence the differentiation and ECM organization of osteogenic progenitor cells. The present study investigates how scaffold fibre orientation affects the behaviour of mature and progenitor osteogenic cells, the influence on secreted mineralized-collagenous matrix organisation, and the resulting construct mechanical properties. Gelatin-coated electrospun poly(caprolactone) fibrous scaffolds were fabricated with either a low or high degree of anisotropy and cultured with mature osteoblasts (MLO-A5s) or osteogenic mesenchymal progenitors (hES-MP). For MLO-A5 cells alkaline phosphatase (ALP) activity was highest and more calcium-containing matrix was deposited onto aligned scaffolds. In contrast, hES-MPs, osteogenic progenitor cells, exhibited higher ALP activity, collagen and calcium deposition on randomly orientated fibres compared with aligned counterparts. Deposited matrix was isotropic on random fibrous scaffolds whereas a greater degree of anisotropy was observed in aligned fibrous constructs, as confirmed by second harmonic generation and SEM imaging. This resulted in anisotropic mechanical properties on aligned constructs. This study indicates that mineralized-matrix deposition by osteoblasts can be controlled by scaffold alignment but that the early stages of osteogenesis may not benefit from culture on orientated scaffolds.